EVALUASI KOMPOSISI SERAT KASAR DAN KECERNAAN RUMEN IN VITRO TANDAN KOSONG KELAPA SAWIT TEKNOLOGI AMONIASI FERMENTASI DENGAN EM-4 DAN CAIRAN RUMEN SAPI (Evaluation of crude fiber composition and in vitro rumen digestibility of empty palm bunches.....) - Julianti, Erma; Harahap, Rakhmad Perkasa; Rohayeti, Yeti (Universitas Nusa Cendana, 2024)
Empty oil palm fruit bunches (OPEFB) have the potential as ruminant livestock feed, but their quality needs to be improved. This study evaluated the effectiveness of fermentation ammonia technology with EM-4 and cattle rumen fluid in improving the nutritional quality and digestibility of OPEFB in vitro. The study used a randomized block design (RBD) with four treatments and six replications: P0 (2 kg OPEFB), P1 (2 kg OPEFB + 40 g urea + 60 ml molasses), P2 (2 kg OPEFB + 40 g urea + 60 ml molasses + 60 ml EM-4), and P3 (2 kg OPEFB + 40 g urea + 60 ml molasses + 60 ml cattle rumen fluid). Descriptive statistical analysis was performed on the content of crude fiber (CF), neutral detergent fiber (NDF), acid detergent fiber (ADF), and hemicellulose. Dry matter digestibility (DMDi) and organic matter digestibility (OMDi) were analyzed using ANOVA and Duncan's test at the 5% level. The results showed that the P2 treatment decreased the content of CF, NDF, ADF, and hemicellulose descriptively. The decrease in fiber components in treatments P1, P2, and P3 compared to the control (P0) showed the effectiveness of fermentation ammoniation in improving feed quality. Treatment P2 significantly increased DMDi and OMDi in vitro compared to other treatments (P<0.05). Treatments P1 and P3 also increased digestibility compared to P0, although not as high as P2. In conclusion, fermentation ammoniation technology with EM-4 and rumen fluid in OPEFB can decrease the content of CF, NDF, ADF, and hemicellulose, and increase DFM and OMF compared to the control.